Photoelectrochemical Hydrogen Generation and Concomitant Organic Dye Oxidation under TiO2 Nanotube - Zanoni, M. V. B. [UNESP]; Guaraldo, T. T. [UNESP]; Brisard, G.; Wieckowski, A. (Electrochemical Soc Inc, 2013)
The present work describes the photoelectrochemical hydrogen generation during a photodegradation of an organic compound. For this, it was chosen the reactive black 5 dye as a model of organic pollutant and its oxidation under TiO2 nanotube in a two compartment cell. The photoelectrocatalysis is conducted in 0.1 mol L-1 Na2SO4 pH 6 medium under photoanode biased at +1.0 V (SCE) and activated by UV and visible light using 150W Xe-Arc lamp (Oriel) and 125 W Hg lamp (Osram). The concomitant hydrogen production was monitored at cathodic compartment using a Pt cathode. Using optimized condition of Na2SO4 0.1 mol L-1 pH 6 as supporting electrolyte, applied potential of +1.0V it was verified 100% of discoloration and 72% of TOC removal of 1.0 x 10(-5) mol L-1 Reactive Black 5 dye after 120 min of treatment (rate constant of 10.6 x10(-2) min(-1)). The concomitant hydrogen generation was 44% in this condition.